Intrinsic physiological properties of the five types of mouse ganglion-cell photoreceptors - Hu, Caiping (American Physiological Society, 2013)
In the mammalian retina, some ganglion cells express the photopigment melanopsin and function as photoreceptors. Five morphological types of these intrinsically photosensitive retinal ganglion cells (ipRGCs), M1–M5, have been identified in mice. Whereas M1 specializes in non-image-forming visual functions and drives such behaviors as the pupillary light reflex and circadian photoentrainment, the other types appear to contribute to image-forming as well as non-image-forming vision. Recent work has begun to reveal physiological diversity among some of the ipRGC types, including differences in photosensitivity, firing rate, and membrane resistance. To gain further insights into these neurons' functional differences, we conducted a comprehensive survey of the electrophysiological properties of all five morphological types. Compared with the other types, M1 had the highest membrane resistance, longest membrane time constant, lowest spike frequencies, widest action potentials, most positive spike thresholds, smallest hyperpolarization-activated inwardly-rectifying current-induced “sagging” responses to hyperpolarizing currents, and the largest effects of voltage-gated K(+) currents on membrane potentials. M4 and M5 were at the other end of the spectrum for most of these measures, while M2 and M3 tended to be in the middle of this spectrum. Additionally, M1 and M2 cells generated more diverse voltage-gated Ca(2+) currents than M3–M5. In conclusion, M1 cells are significantly different from all other ipRGCs in most respects, possibly reflecting the unique physiological requirements of non-image-forming vision. Furthermore, the non-M1 ipRGCs are electrophysiologically heterogeneous, implicating these cells' diverse functional roles in both non-image-forming vision and pattern vision.